Resistive switching memory based on chitosan/polyvinylpyrrolidone blend as active layers. (1st April 2022) - Dlamini, Zolile Wiseman; Vallabhapurapu, Sreedevi; Wu, Shuying; Mahule, Tebogo Sfiso; Srivivasan, Ananthakrishnan; Vallabhapurapu, Vijaya Srinivasu
Abstract: We report on resistive switching in ReRAM devices that use chitosan/PVP composite as the active layers. Al/chitosan+PVP/Ag and ITO/chitosan+PVP/Ag devices, each consisting of chitosan/PVP active layer having 1:3, 1:1 and 3:1 chitosan to PVP ratio were studied. Asymmetric threshold switching with V t h = − 1 . 21 V and V h o l d = − 0 . 34 V only in the negative voltage bias was obtained for the Al/chitosan+PVP(1:3)/Ag device. The Al/chitosan+PVP(1:1)/Ag device showed better memory behaviour relatively. This device showed bipolar switching with V S E T = + 0 . 75 V, and V R E S E T = − 0 . 28 V, then asymmetric TS with V t h = + 0 . 84 V and V h o l d = + 0 . 19 V and lastly back to bipolar switching with V S E T = + 0 . 77 V and V R E S E T = − 045 V, during the first, second and third voltage sweeping cycles. We attributed the switching in this device to the formation and rupture of conductive filaments due to Ag ions migration. On the other hand, the Al/chitosan+PVP(3:1)/Ag showed no memory behaviour. In comparison, all ITO/chitosan+PVP/Ag devices did not show any memory characteristics. This indicating the role of the Al/chitosan+PVP interface in the Al/chitosan+PVP/Ag system. Furthermore, we observed the possibility of compliance current dependent or sweeping cycle-dependent decrease in resistance and change from linear to exponential current behaviour in ITO/chitosan+PVP/Ag devices. Resistive switching based on chitosan/PVP blend is essential for biodegradable and environmentally friendly devices. Our results reveal the applicability of chitosan/PVP blend in memory device fabrication and that both the memory and switching can be exploited by varying the ratio of chitosan to PVP in the composite. Lastly, our results demonstrate the importance of electrode material in ReRAM devices. Highlights: Resistive switching based on blended chitosan/Polyvinylpyrrolidone is safe for the environment. Blended chitosan/Polyvinylpyrrolidone can be used as the active layer for transparent and flexible emerging resistive switching memory. Optimal resistive switching memory behaviour in blended chitosan/Polyvinylpyrrolidone based ReRAM is achieved at 1:1 chitosan to polyvinylpyrrolidone ratio, and when Al and Ag electrodes are used. Chitosan/polyvinylpyrrolidone blend does not show switching when ITO and Ag electrodes are used. Blended chitosan/polyvinylpyrrolidone based ReRAM show conducting bridge type resistive switching mechanism, associated with metalization of Ag + ions when Ag and Al electrodes are used. Chitosan/polyvinylpyrrolidone blend shows both I C C - and sweeping voltage-dependent increase in conductivity when ITO and Ag electrodes are used.